Perspectives in poverty and mental health - Marbin, Derin; Gutwinski, Stefan; Schreiter, Stefanie; Heinz, Andreas (Frontiers in Public Health, 2022)
In recent years, different forms of poverty and their interaction with mental illness have been in the focus of research, although the implementation of action in mental health care and policy making so far is scarce. This perspective article offers different perspectives of poverty and its reciprocal association with mental illness and outlines possible future research and policy implications. We will approach the topic of poverty from various levels: On a micro-level, focusing on absolute poverty with precarious housing and malnutrition. On a meso-level, on neighborhood-related poverty as a factor in individuals' mental illness. On a macro-level, on effects of income inequality on mental health. In several studies, it has been shown that on each level, poverty has a profound impact on mental health, though it must be noted that in some fields, research is still scarce. In the future, an inter- and transdisciplinary approach is of considerable importance, since poverty and its impact on mental health should be addressed from different perspectives, reaching from targeted programs for individual groups (e.g., homeless people) up to national policy measures.